Pengembangan Modul Berbasis STEM pada Materi Inovasi Bioteknologi untuk Siswa Fase F (SMA/MA) - Wina Oddessi Putri; Renny Risdawati; Aulia Afza (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to develop a STEM (Science, Technology, Engineering, and Mathematics)-based module on biotechnology innovation material for Phase F SMA/MA students, and to test its validity and practicality. This study is a developmental research that refers to the 4D model proposed by Sivasailam Thiagarajan, including the define, design, and develop stages. The research subjects consisted of four validators (three lecturers and one teacher), one biology teacher, and 26 students of grade XII Phase F at SMA Negeri 2 Padang. The instruments used were a validity questionnaire and a practicality questionnaire with a modified Likert scale. The results of the validity test showed that the developed STEM-based module obtained an average score of 95.42% with very valid criteria. Details of each aspect include content feasibility (98%), language (100%), presentation (97.1%), graphics (92%), and STEM components (90%). After revisions according to the validator's suggestions, the module was declared suitable for use. The practicality test results obtained an average score of 86%, categorized as very practical, by teachers, and 89.50%, categorized as very practical. Aspects assessed included ease of use, efficiency of learning time, and the module's usefulness in the learning process. Based on these results, it can be concluded that the STEM-based module on biotechnology innovation for Phase F high school/Islamic high school students is highly valid and practical, making it suitable for use as a teaching material in biology lessons to support critical thinking, problem-solving, and independent learning skills.